O uso do aplicativo hidrocarbonetos como ferramenta no processo de aprendizagem no ensino de Química - COSTA, Helem Fabiana Reis da (2022)
This work was developed in order to verify how the use of applications used as tools in the teaching of Chemistry can help in the development of the teaching-learning process. The objective of this study was to analyze the use of the Hidrocarbonetos application with students from the Integrated Technician in Informatics classes of the Escola de Ensino Médio Prof. Maria de Nazaré Guimarães Macedo, located in the Municipality of Curuçá-PA. The research was carried out through the questionnaires applied, after using the application and investigating the relationship between the questionnaire carried out after a lecture and the other questionnaire carried out after using the application. It was possible to perceive that when the technology is well applied, considering it as a tool to aid in teaching, the results are positive in a satisfactory way.